Lipid Emulsion Attenuates Acetylcholine-Induced Relaxation in Isolated Rat Aorta. (27th July 2015) - Ok, Seong-Ho; Lee, Soo Hee; Yu, Jongsun; Park, Jungchul; Shin, Il-Woo; Lee, Youngju; Cho, Hyunhoo; Choi, Mun-Jeoung; Baik, Jiseok; Hong, Jeong-Min; Han, Jeong Yeol; Lee, Heon Keun; et al.
Abstract : We investigated the effect of Lipofundin MCT/LCT and Intralipid on acetylcholine-induced nitric oxide- (NO-) mediated relaxation in rat aorta to determine which lipid emulsion (LE) is more potent in terms of inhibition of NO-induced relaxation. Dose-response curves of responses induced by acetylcholine, the calcium ionophore A23187, and sodium nitroprusside were generated using isolated rat aorta with or without LE. The effect of Lipofundin MCT/LCT on acetylcholine-induced endothelial nitric oxide synthase (eNOS) phosphorylation in human umbilical vein endothelial cells (HUVECs) was investigated using western blotting. Lipofundin MCT/LCT (0.1 and 0.2%) attenuated acetylcholine-induced relaxation in endothelium-intact aorta with or without tiron, whereas 0.2% Intralipid only inhibited relaxation. Lipofundin MCT/LCT inhibited relaxation induced by the calcium ionophore A23187 and sodium nitroprusside in endothelium-intact aorta, but Lipofundin MCT/LCT had no effect on sodium nitroprusside-induced relaxation in the endothelium-denuded aorta. Combined pretreatment with l -arginine plus Lipofundin MCT/LCT increased acetylcholine-induced maximal relaxation in endothelium-intact aorta compared with Lipofundin MCT/LCT alone. l -Arginine attenuated Lipofundin MCT/LCT-mediated inhibition of acetylcholine-induced eNOS phosphorylation in HUVECs. Taken together, Lipofundin MCT/LCT attenuated acetylcholine-induced NO-mediated relaxation via an inhibitory effect on the endothelium including eNOS, which is proximal to activation of guanylyl cyclase.